If you first factor out a common 2, then you have:
2 (x² - x - 6)
Now this factors to:
2 (x - 3)(x + 2)
So your answers are x = 3 and x = -2
As a double-check:
2(3²) - 2(3) - 12 = 0
2(9) - 6 - 12 = 0
18 - 6 - 12 = 0
18 - 18 = 0 <-- check, so x = 3
2(-2)² - 2(-2) - 12 = 0
2(4) - (-4) - 12 =0
8 + 4 - 12 = 0
12 - 12 = 0 <-- check, so x = -2
2006-12-26 13:15:39
·
answer #1
·
answered by Puzzling 7
·
3⤊
0⤋
First: find a number divisible by the coefficients > (2). Take (2) and bring it to the front; multiply (2) by missing terms in the parenthesis:
2(x^2 - x - 6) = 0
Second: factor the inside. Take the first coefficient and multiply it by the last coefficient = (1)(-6) = -6. Find two numbers that give you (-6) when multiplied and -1 (middle coefficient) when added/subtracted. The numbers are: -3, 2
2(x - 3)(x + 2) = 0
Third: set each term to equal zero > exclude 2 > it doesn't = 0
x - 3 = 0
x - 3 + 3 = 0 + 3
x = 3
x + 2 = 0
x + 2 - 2 = 0 - 2
x = -2
(3, -2)
2006-12-26 13:20:14
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
2⤊
0⤋
Solve 2x 12
2017-01-09 13:14:46
·
answer #3
·
answered by ? 3
·
0⤊
0⤋
2x² - 2x - 12 = 0
2x² - 6x + 4x - 12 = 0
2x(x - 3) + 4(x - 3)
(2x + 4)(x - 3)
- - - - - - - - - - -
Roots
2x + 4 = 0
2x + 4 - 4 = 0 - 4
2x = - 4
3x/2 = - 4/2
x = - 2. . .<=. .Not used
- - - - -
x - 3 = 0
x - 3 + 3 = 0 + 3
x = 3
The answer is x = 3
Insert the x value into the equation
- - - - - - - - - - -
x² - 2x - 12 = 0
2(3)² - 2(3) - 12 = 0
2(9) - 6 - 12 = 0
18- 6 - 12 = 0
12 - 12 = 0
0 = 0
- - - - - - -s-
2006-12-27 01:29:13
·
answer #4
·
answered by SAMUEL D 7
·
1⤊
0⤋
The correct factorization is (2x-6)(x+2)
= 2x^2+4x-6x-12
=2x^2-2x-12
In this case because the equation is not monic (the leading coefficient is 2 not 1) then you need two numbers that multiply to
a * c = 2 * -12 = -24
and add up to b = -2
where a, b, and c are the coefficients of the quadratic ax^2+bx+c
Here, you have -6 and 4 satisfy the two conditions above, mult to -24 and add up to -2
You use the -6 and 4 to break up the middle term and solve by grouping as follows:
The middle term -2x becomes -6x + 4x
2x^2 - 6x + 4x -12
Factor out 2x from the first two terms and 4 from the last two terms:
2x ( x-3) + 4 (x-3) = (2x+4) (x-3) = 0
This gives you x=-2 and x=3
You could also have done:
2x^2 + 4x - 6x - 12
2x (x+2) - 6 ( x+2) = (x+2) (2x-6) again giving you x=-2, x=3
2006-12-26 13:20:55
·
answer #5
·
answered by Professor Maddie 4
·
1⤊
2⤋
1) The first method:
(2x-6)(x+2)=0
2x=6
x=-2
x= 3 or -2
2) The second method:
Factor out a 2:
2(x^2-x-6)=0
(x+2)(x-3)=0
x+2=0
x-3=0
x=-2 or 3
I hope this helps you with your homework!
2006-12-27 09:29:30
·
answer #6
·
answered by Anonymous
·
2⤊
0⤋
2x^2 - 2x - 12 = 0
(2x - 6)(x + 2) = 0
2x - 6 = 0 or x + 2 = 0
2x = 6
x = 3
or
x + 2 = 0
x = -2
x = 3 or x = -2
QED
2006-12-27 09:29:57
·
answer #7
·
answered by CSUFGrad2006 5
·
2⤊
1⤋
You're close but (2x+6)(x-2) = 2x^2 + 6x - 4x - 12 = 2x^2 PLUS 2x - 12
You need to reverse the signs: (2x-6)(x+2)
2x-6=0 yields x=3
x+2 = 0 yields x= negative 2
2006-12-26 13:18:07
·
answer #8
·
answered by firefly 6
·
2⤊
0⤋
2x²-2x-12=0
Factoring:
x² - x - 6 = 0
(x - 3) (x + 2) = 0
x' = 3
x" = -2
or
Justify:
delta = b² - 4ac
delta = -1² - 4.1.-6
delta = 1 + 24 = 25
x = (-b +/-\/delta) : 2a
x = (-(-1) +/-5) : 2.1
x' = (1 + 5): 2 = 3
x" = (1 - 5) : 2 = -2
Solution: {x E R | x = 3 or x = -2}
Happy New Year!
<>
2006-12-26 14:51:06
·
answer #9
·
answered by aeiou 7
·
1⤊
0⤋
You left out a negative sign.
2x+6=0
2x= -6
x= -3
2006-12-26 13:15:49
·
answer #10
·
answered by Jimmy H 1
·
0⤊
2⤋